Markey’s Denial to Cope Grief in Niven’s All the Bright Places - Nariswari Hartati; Mia Fitria Agustina; Ririn Kurnia Trisnawati (Metathesis: Journal of English Language, Literature, and Teaching, 2022)
The object of this study is All the Bright Places (2015), a young adult fiction novel which tells a story about two teenagers and their problems related to their mental illness. The interesting topic which became the main discussion in this study is how the female character of this novel, Violet Markey, using denial as her defence mechanism to cope grief on her sister and boyfriend’s death. To examine this topic, the researchers used descriptive qualitative method. This study found that in order to cope with Markey’s sister death, Markey used self-protective function of denial, while to cope with Finch’s death, her form of denial is by refusing to acknowledge his death.